IDEOLOGY AND POLITICS PROFESSORS AND STUDENTS IN THE CONTEXT OF THE ARGENTINE LIBERAL CRISIS. THE CASE OF THE UNIVERSIDAD DE CÓRDOBA (1930-1943) - Antonio Sillau Pérez, María Cristina Vera de Flachs, (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
Worried about the universities history, investigators generally analyze the activities of these institutions as if these were free from politics and think that their internal conflicts are far from them. Sharing other erudites’ criteria, we disagree with that analysis. For that reason, this article intends to demonstrate how politics and ideas interweave in a political-ideological struggle in a period of the history of Universidad Nacional de Córdoba that went from 1930 to 1943. This transition stage, which testifies a deepening process of the multidimensional crisis of the liberal project of modern Argentina, registers its origins in the political scope by beginning with the military coup of September 6 of 1930 that overthrew the democratic regime of the radical Hipólito Yrigoyen and concluded with another “revolution”, the one of June 4 of 1943. This would open new hopes for the nationalists, who would soon realize that their expectations were not going to come true while the regime of “nueva cristiandad” or “Christian Totalitarianism” would not get crystallized. Any way the “old Argentina” and its historical bequest of the 80’s would come to its end. The confrontations lived in the university between the nationalistic and reformist groups were not exempt of reflecting the complex political panorama and the ideological interweaving that appeared in the dialectics of the political game at national and international scale. As a consequence, in this regard, and related to these politico-ideological transformations, both professors’ and students’ politization are detailed, recognizing their repercussion in both praxis and evolution of the university policy.